The Effect of Cymbopogon Citratus Aromatherapy on Preoperative Patient Anxiety: A Literature Review - Adelia Fenanda Puspitasari; Fahrun Nur Rosyid (Indonesian Journal of Global Health Research, 2025)
Surgery is a medical procedure that involves an invasive approach by opening a specific body part to address a medical issue. Preoperative patients often experience anxiety. Lemongrass aromatherapy is one of the therapies that utilizes essential oils to promote and maintain health, stimulate, refresh, and uplift the body while reducing anxiety. This study aims to review the effectiveness of Cymbopogon citratus aromatherapy in reducing anxiety in preoperative patients. A literature review was conducted by searching articles from ScienceDirect, PubMed, and Google Scholar using advanced search techniques with the keywords “preoperative, anxiety, lemongrass aromatherapy.” The articles used in this literature review are from 2020-2025, which match the title of the article and meet the inclusion and exclusion criteria. Cymbopogon citratus aromatherapy has been found to be significantly effective in reducing anxiety across various conditions, including preoperative patients, maternity patients, and individuals undergoing other medical procedures. The use of Cymbopogon citratus aromatherapy can be an effective complementary intervention to reduce anxiety in preoperative patients.